Scottish Court of Session : Digital Archive Project : A Multi-Institutional Collaborative Research Initiative into Early America and the British Atlantic World - University of Virginia - Library (2021)
"The Scottish Court of Session Digital Archive Project is an initiative to explore everyday life in early America and the British Atlantic world of eighteenth and early nineteenth centuries through Session Papers. These printed materials were submitted to Scotland's supreme civil court as part of the litigation process. As a court of appeal and of first instance, the Court of Session in this period held jurisdiction over contract and commercial cases, matters of succession and land ownership, divorce proceedings, intellectual property and copyright disputes, and contested political elections. Scottish women, Virginia merchants, aristocratic Highland proprietors, famous authors, enslaved laborers, soldiers, American Loyalists, and many more individuals sought justice before the Court of Session in this era. The documents offered in this archive date from the late 1750s to the late 1830s, a period encompassing the Seven Years' War in North America and the Great Reform Act in Scotland." [self-description]